(untitled) (Journal of Hama University, 2022)
Diabetes mellitus is one of the widespread diseases in the modern era and negatively affects the functional performance and quality of life of patients, as it is a chronic disease that leads to disability and patients need lifelong care. The quality of life of patients is severely affected by this disease. Purpose: The aim of this study was to assess the quality of life among Diabetic patients, Methods: A descriptive Correlation study was performed using a convenience sample of 400 diabetic patients of Diabetes Center in Lattakia, during the period of 15 February to 15 May 2021, data were collected using the WHO Short Quality of Life Scale. Results: The results showed that the level of quality of life was middle level, and Domains of Physical health, Psychological, Social relationships and Environment were middle level . Conclusion and Recommendations: the study suggest increasing attention to diabetic patients by governmentalism institutions, especially the Ministry of Health, for attention to the quality of health services provided to them. And conducting educational courses and programs for patients regarding care and counseling for patients about diabetes and its impact on the level of quality of life, and the inclusion of the quality of life measure within the treatment plan, more studies that reflect this erea on the diabetic patients population should be conducted with a larger sample size .